STUDY ANALYSIS OF ORAL TUBERCULOSIS LESION IN SOUTH KALIMANTAN, INDONESIA - Apriasari, Maharani Laillyza; Silalahi, Monita Valentine; Hatta, Isnur; Utami, Juliyatin Putri (Odonto : Dental Journal, 2020)
Background: Tuberculosis is an infectious disease which is the second-largest cause of death in the world after HIV / AIDS. Tuberculosis caused by Mycobacterium tuberculosis that usually attacks the lungs but can manifest in the oral mucosa. Clinical manifestations of oral Tuberculosis related to age, sex, duration of treatment, systemic disease, and Multi-Drug Resistant therapy. There is no research on descriptive studies of oral manifestations of tuberculosis patients in South Kalimantan, specifically in Banjarmasin. This study aims to analyze the clinical manifestations of oral Tuberculosis descriptively in South Kalimantan, Indonesia. Method: This was a descriptive analysis with cross-sectional study design, based on history and clinical oral examination. It was used 30 respondents by purposive sampling method. Data were analyzed by Chi-square (p<0.05). Results: During treatment, it showed the correlation between xerostomia and systemic disease (diabetes mellitus and HIV/AIDS) are (p=0.007) and a correlation between xerostomia and duration of treatment (p=0.024). The correlation between candidiasis and systemic disease (p=0.024). The correlation between angular cheilitis and age, sex, duration of treatment, systemic disease, and Multi-Drug Resistant therapy (p>0.05). The clinical manifestations of oral Tuberculosis are xerostomia, candidiasis, and angular cheilitis.Conclusion: The duration of treatment and the systemic diseases are associated with xerostomia and candidiasis in the oral cavity of TB patients.